2020
DOI: 10.1038/s41598-020-61196-8
|View full text |Cite
|
Sign up to set email alerts
|

Organisational Social Influence on Directed Hierarchical Graphs, from Tyranny to Anarchy

Abstract: Coordinated human behaviour takes place within a diverse range of social organisational structures, which can be thought of as power structures with "managers" who influence "subordinates". A change in policy in one part of the organisation can cause cascades throughout the structure, which may or may not be desirable. As organisations change in size, complexity and structure, the system dynamics also change. Here, we consider majority rule dynamics on organisations modelled as hierarchical directed graphs, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Directionality can also have a crucial effect on dynamical systems. In previous work we have shown, for instance, that trophic coherence is sometimes a determining factor in ecosystem or social stability [9,13], or whether spreading processes such as epidemics will become endemic [14]. And both trophic coherence and non-normality are reflected in graph eigenspectra, which in turn can be related with the stability of dynamical systems [8,10].…”
Section: The Importance Of Being Directedmentioning
confidence: 98%
“…Directionality can also have a crucial effect on dynamical systems. In previous work we have shown, for instance, that trophic coherence is sometimes a determining factor in ecosystem or social stability [9,13], or whether spreading processes such as epidemics will become endemic [14]. And both trophic coherence and non-normality are reflected in graph eigenspectra, which in turn can be related with the stability of dynamical systems [8,10].…”
Section: The Importance Of Being Directedmentioning
confidence: 98%
“…The interplay between trophic structure and dynamics has already been observed across a range of systems in the literature [14,18,22]. It has also been shown that the coherence of a network is linked to the non-normality of the adjacency matrix [1,4] (i.e.…”
Section: Discussionmentioning
confidence: 86%
“…This is the definition that will be used in this work. Trophic structure has been used to study spreading processes in neural and epidemiological settings [14], infrastructure [20,21] and the structure of organisations [22]. Trophic Analysis is composed of two parts: the node level information, Trophic Level, which describes where each node sits in the overall hierarchy of a network; and the global information of how directed, or coherent, the overall network is.…”
Section: Using Trophic Analysis To Quantify Network Hierarchymentioning
confidence: 99%
“…Loosely speaking, the hierarchical level of any node i is defined as the shortest path from a top-node to node i. More precisely, the level is defined as the trophic hierarchical level [49,50]. We have analyzed the Reddit discussion forum for the Blackberry meme stock (see Section 5 below).…”
Section: Parametrization Of Non-normal Matrices With Level-dependent ...mentioning
confidence: 99%